Angiosarcoma of the prostate: a more frequent finding in the future owing to radiotherapy? A literature review with treatment implications based on a case report. (October 2014) - Campschroer, Thijs; van der Kwast, T. H.; Jonges, G. N.; Lock, M. T. W. T.
Abstract Objective. An increase in the incidence of prostate angiosarcoma may be expected owing to the exponential increase in the use of radiotherapy for prostate carcinoma in recent decades and the possible aetiology of radiation exposure on the development of angiosarcoma in general. The objective of this study was to give an overview of cases in the literature based on a case report of prostate angiosarcoma in a hospital in the Netherlands, and to discuss optimal treatment. Material and methods. All (related) articles In PubMed/Medline and Embase with possible cases of angiosarcoma were screened on title and abstract. A case of prostate angiosarcoma identified in the authors' institution was included. Results. The literature search yielded 13 cases of prostate angiosarcoma. The earliest six publications lack essential data. Four patients had a history of radiotherapy. The present patient developed angiosarcoma following brachytherapy for prostate cancer. Therapy consisted of radical surgery with or without chemotherapy in five cases. In eight cases curative therapy was not reported or not possible. Mean follow-up was only 1 year. Four patients died within 1 year of diagnosis, irrespective of treatment choice. One patient, treated with a combination of radical surgery and adjuvant chemotherapy, was still alive 36 months after therapy. Conclusions. The findings confirm that prostate angiosarcoma is mostly radiation induced. This patient is the first case of prostate angiosarcoma after primary brachytherapy. Angiosarcoma may occur more often in the future owing to widespread use of brachytherapy and radiotherapy of the prostate. Current guidelines on management of angiosarcoma suggest radical surgery in local disease as the primary treatment of choice.